2005
DOI: 10.3171/spi.2005.3.3.0224
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic transfacet pedicle screw fixation: a new instrumentation technique

Abstract: Object. Pedicle screw instrumentation of the thoracic spine remains technically challenging. Transverse process and costotransverse screw fixation techniques have been described as alternatives to pedicle screw fixation (PSF). In this study, the authors introduce thoracic transfacet PSF and compare its experimental biomechanical results with those of standard PSF in short-term cyclic loading in cadaveric thoracic specimens. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Transfacet pedicle screws (TFPSs), placed through the facet joint extending into the pedicle, provide another alternative to the traditional pedicle screw fixation technique (Figure 3c) (128). According to biomechanical studies, both techniques are reported to have comparable strength in both thoracic and lumbar spine fixation (128,129).…”
Section: Facet Joint Fusion Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfacet pedicle screws (TFPSs), placed through the facet joint extending into the pedicle, provide another alternative to the traditional pedicle screw fixation technique (Figure 3c) (128). According to biomechanical studies, both techniques are reported to have comparable strength in both thoracic and lumbar spine fixation (128,129).…”
Section: Facet Joint Fusion Systemsmentioning
confidence: 99%
“…Transfacet pedicle screws (TFPSs), placed through the facet joint extending into the pedicle, provide another alternative to the traditional pedicle screw fixation technique (Figure 3c) (128). According to biomechanical studies, both techniques are reported to have comparable strength in both thoracic and lumbar spine fixation (128,129). The minimally invasive nature of this technique is promising, but additional long-term data are necessary to evaluate its safety and ability to achieve solid fusion (130,131).…”
Section: Facet Joint Fusion Systemsmentioning
confidence: 99%
“…Biomechanical studies have shown that lumbar transfacet pedicle screw is biomechanically equivalent to the pedicle screw [18,19]. Akbay et al [20] used the transfacet pedicle screw in the middle and lower thoracic spine to compare its experimental biomechanical result with that of standard pedicle screw. Indeed the technique of transarticular screw fixation in our investigation is different with transfacet pedicle screw fixation.…”
Section: Discussionmentioning
confidence: 98%
“…The Viper F2 system was found to be equivalent to the existing Viper 2 system in all ranges of motion (flexion extension, lateral bending, and axial rotation), and analysis details available in separate publications [11][12][13][14][15][16][17][18][19][20]21]. This technique is expensive, requires expertise in tissue testing, and only provides comparative in vitro performance in a model not fully representative of the real clinical environment.…”
Section: Biomechanical Testingmentioning
confidence: 99%
“…The new Viper 2 system relies on directly fixing the spine using the vertebral facets via only one screw and washer per side. Simple facet screws have been used several decades ago with mixed clinical success [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Due to the popularity of minimally-invasive-surgery (MIS) in recent years, there is a renewed interest in more sophisticated MIS facet screw systems coupled with washers, expected to provide clinical performance equivalent to pedicle screws and rods, while minimizing operating room time, blood loss, cost and surgical trauma.…”
Section: Businessmentioning
confidence: 99%